2016
DOI: 10.5901/mjss.2016.v7n6p121
|View full text |Cite
|
Sign up to set email alerts
|

Study on Determinant Factors of Micro and Small Enterprises Development in South Sulawesi of Indonesia

Abstract: The purposes of this study is to examine factors determinants of development of micro and small enterprises in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…Financially sound MSME managers often avoid taking on more debt than can afford to repay, save, invest, and handle their money. a mediator is provided, where business performance is defined as a condition demonstrating company growth, as measured by growth in labor, capital, sales, market expansion, and profits [47][48][49]. A mapping of study findings demonstrating the impact of financial literacy on company success is presented in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financially sound MSME managers often avoid taking on more debt than can afford to repay, save, invest, and handle their money. a mediator is provided, where business performance is defined as a condition demonstrating company growth, as measured by growth in labor, capital, sales, market expansion, and profits [47][48][49]. A mapping of study findings demonstrating the impact of financial literacy on company success is presented in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Belanja pembangunan desa dan belanja pemberdayaan masyarakat yang dialokasikan untuk kepentingan industri perdesaan menjadi sebuah kebijakan probisnis dari pemerintah desa. Sebagaimana disampaikan Wilkinson (2002) dalam Munizu et al (2016) bahwa kebijakan semacam itu dapat membantu perkembangan industri perdesaan. Alokasi belanja untuk kepentingan industri memberikan kesempatan yang lebih besar terhadap perkembangan industri perdesaan.…”
Section: Modal Sosialunclassified
“…The study found that government schemes sometimes do not reach needy people due to corruption. Munizu (2016) examined factors determinants of the development of micro and small entrepreneurs in Indonesia. The research was based on primary data.…”
Section: Literature Reviewmentioning
confidence: 99%